Stress state in forward cold extrusion - Plančak, Miroslav; Vilotić, Dragiša; Kačmarčik, Igor (Advanced Technologies and Materials, 2014)
Cold extrusion of steel and other metallic materials is a technology which enables manufacturing of small and middle size parts with high mechanical properties and accuracy in very short cycle time. Limitations are related to the high contact pressures which can occur between the die and working material and – in some cases – to the exhaustion of material formability. Formability potential of forward extrusion of low carbon steel specimen has been investigated in this paper. Concept of Forming Limit Curve (FLC) introduced by Vujovic and Shabaik was applied to perform formability analysis. Complete stress state in the forming zone has been determined by using visioplasticity method. Results of current investigation have shown that only a small portion of the forming volume lies in the „dangerous zone“ , i.e. in the zone where cracks are likely to occur. However, in the experiments no cracks („shevron formation“) could be detected.